ANALYSIS OF FACTORS AFFECTING SERVICE DOG TRAINING - Khasanov Maksudali Makhmudovich (Scholar Express Journals, 2023)
This article describes the history of the canine service in the Republic of Uzbekistan, the importance of using service dogs and the objective necessity of using service dogs in the activities of law enforcement agencies today, as well as the importance of factors affecting the effectiveness of service dogs in the effective use of service dogs. Also in the article there is a specific proposal for the development of work in this regard on a scientific basis and recommendations are given
Keywords: human evolution; pets; general training course; service dog efficiency